Estudo teórico do efeito de micro-solvatação na molécula ácido orto-Aminobenzóico (o-Abz) - Pachêco, Vanusa Bezerra (Universidade Federal de São Carlos, 2013)
In this work we analyzed the effect microsolvation in the electronic properties of the molecule ortho-aminobenzóic (o-Abz) in the gas phase using the solvent water. For this we considered two situations, one in that the solvent water molecule are placed close to the carboxyl group and another that the water molecule are placed close to the amino group producing the clusters o-Abz ⋯⌈H2O⌉...(continue).
Keywords: Micro-hidratação; Ligação de hidrogênio; Ácido orto-Aminobenzóico (o-Abz); CIENCIAS EXATAS E DA TERRA::FISICA